Exploring the social impacts of the tourism sharing economy from a hospitality perspective - van den Brink, Tess (fi=Lapin yliopisto|en=University of Lapland|, 2019)
The present study focusses on the hospitality in, and social impacts of, the tourism sharing economy from the perspective of Airbnb hosts and their neighbours. The study addresses the need to understand the role of hospitality in the sharing economy following growing expressed disapproval of it as reported by the media. The study aimed to fill the academic gap on the impacts of the sharing economy in smaller destinations. This study adopts an interpretive/constructive approach in the abstraction of categories, ideas and concepts – with the purpose of implying generalisability while answering the different research questions. These research questions focussed on the following (1) the conceptualisation of ‘hosts’ and ‘guests’ in the tourism sharing economy, (2) the conceptualisation of hospitality in the tourism sharing economy, (3) the role of neighbours in relation to hospitality in the tourism sharing economy, and (4) the perceived social impacts of the tourism sharing economy and the categorisation thereof. The data was collected through interviews with Airbnb hosts and their neighbours, from two relatively small European destinations: arctic tourism destination Rovaniemi in Lapland, Finland and university suburb Castletroy in Limerick, Ireland. The analysis revealed that a big influence on the hospitality in the tourism sharing economy is Airbnb’s ‘Superhost’ reward system, which puts more pressure on hosts, but also encourages them to go the extra mile for their guests. The tourism sharing economy has not caused major grievances among residents in Limerick or Rovaniemi. It was expressed by both Airbnb hosts and neighbours that the negative impacts of Airbnb are outweighed by the positive impacts. These perceived social impacts can be labelled under the categories: (1) Standard, (2) Social interaction, (3) Ego-economic, (4) Way of life, (5) Personal and public property, (6) Social comfort, and (7) Fear.